PERAN POLRI DALAM PENANGGULANGAN PREMANISME UNTUK MENGAMANKAN PROGRAM PRIORITAS NASIONAL DI PELABUHAN (STUDI DI POLRES PELABUHAN BELAWAN) - Tito Travolta Hutauruk; Madiasa Ablisar; Mahmud Mulyadi; Suhaidi Suhaidi (Universitas Sumatera Utara, 2017)
ABSTRACT The thuggery handling conducted by the Police to support the National priority program at Pelabuhan is done by penal approach that is oriented to the act of cleaning and eradicating thuggery as it has been formulated in the program of wins ProMoTer Kapolri and Commander Wish Head of North Sumatra Regional Police. Another approach is a non-penal approach that is more oriented to preventive actions from potential startup to disturbance threshold, such as conducting activities oriented to problem-oriented policing and strengthening synergy. In addition, the role of the National Police in the handling of thuggery is expected not as a tool of ruling but as an institution that upholds human rights by no longer putting forward violence, more to approach system thinking, knowledge, skill and atitude through soft reform Skil. This is the basic framework of the Police professionalism. In the case of the Police, especially the Belawan Port Resort Police has not been optimal in the handling of thuggery, it certainly has implications for the cleaning program of thuggery as outlined in the policy and strategy of North Sumatra Regional Police and regional development. KeyWords : Role of Police, Thugs, National Priority Program at Port.